EFFECT OF PARTICLE SIZE AND SURFACE CHARGE ON THE UPTAKE AND IMMUNE RESPONSE OF OVALBUMIN-ALGINATE MICROSPHERES - Dewi Melani Hariyadi; Idha Kusumawati; Fauzia Azzahra (UPT Penerbitan Universitas Jember)
Microspheres as one of drug and protein deliverysystem have some advantages such as producingsmall particles; protect extreme conditions andother benefits. Microspheres as one ofparticulate systems have benefits in vaccinedelivery systems for enhancing immune responsethrough several mechanisms. As vaccine deliverysystem, the particles can through phagocytosisdeliver antigens to Antigen Presenting Cells (APC)(Foged et al, 2005). Particulate antigens mightmediate the induction of both humoral andcellular immunity.The particle size, surface charge andphysicochemical properties are factors that affectthe uptake of particles from the gut. Zetapotential may also influence the drug releaseprofiles, stability and physicochemical properties.Microparticles or nanoparticle surface is a veryimportant consideration in drug delivery ystem,especially in targeting drug delivery. Surfacemodification of micro/nano-drug delivery systemsis the most common strategy to controlling theopsonization process and thus sustains thesystems for longer period in the blood stream.Zeta potential is one of important propertieswhich contribute to the effectiveness. Zetapotential can be defined as the electrokineticvalue associating a realistic magnitude of surfacecharge and its unit is usually millivolt.There are some investigations that showed thatthe surface charge of nano/microparticles has aneffect on the stimulation of the immuneresponse. Some studies showed that antigenloaded cationically charged particles could bebeneficial for gut up take (Honary S and Zahir F,2013).Peyer's patches (PP) is the main target of oraldelivery systems in the small intestine as a placefor the transport of pathogens to the lymphoidtissue. This function is carried out by M-cellswhich are located between epithelial cells,bringing antigens and microparticles measuringless than 10 μm (Lubben et al, 2001).This study used alginate microspheres containsafe and biodegradable polymer and CaCl2 nontoxic crosslinking agent produced by gelationionotropic technique by aerosolisation. Thistechnique had the advantage of spherical shape,smooth with a small particle size that meets therequirements of particle size for oral deliverysystems (Hariyadi et al, 2014). Maltodextrinlyoprotectant were found to stabilizemicrospheres (Hariyadi et al, 2015). Ovalbuminwas used as model antigen.The hemagglutination assay was used to evaluatethe formation of antibody and ability to stimulateimmune response. Uptake microspheres werestudied using fluorescent label microscopically. Inthe present study we addressed the importanceof particle size and surface charge for efficientinteractions and effect on the immune response.